2013
DOI: 10.2478/amm-2013-0108
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Applicability of Austempered Ductile Iron Containing Mo and Ni for Mining Machines Parts

Abstract: The research described in this article is a fragment in the series of published works trying to determine the applicability of new materials for parts of the mining machinery. Tests were carried out on the -very popular in mining applications -36HMN steel and three types of the austempered ductile iron, using special stand for the controlled abrasion testing of samples subjected to the effect of loose abrasive. Tests carried out with the use of corundum showed the competitive properties of cast iron as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The reason of a high wear resistance is most likely the transition of austenite into martensite occurring in the surface layer under a load. The authors analysed the problem of the phase transitions occurring in cast irons containing Ni and Cu in their earlier study [9]. They found, inter alia, a distinct correlation between the content of metastable austenite and an increase in the surface hardness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason of a high wear resistance is most likely the transition of austenite into martensite occurring in the surface layer under a load. The authors analysed the problem of the phase transitions occurring in cast irons containing Ni and Cu in their earlier study [9]. They found, inter alia, a distinct correlation between the content of metastable austenite and an increase in the surface hardness.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors, including Schissler et al [5], Owhadi et al [6], Hayrynen et al [7,8], Myszka and Wieczorek [9,10] confirmed a beneficial influence of the strain-induced transition on the wear properties of ADIs.…”
Section: Introductionmentioning
confidence: 99%
“…They substantiated this fact by a low resistance of graphite to microcutting and by propagation of microcracks from spots formed after the destruction of the graphite nodules. Myszka and Wieczorek [11] performed wear tests for 34CrNiMo6 hardened steel and three types of austempered ductile iron containing Mo and Ni. Wear tests showed that the cast iron had properties comparable to those of the steel tested and that the wear resistance of ADI was increasing along with an increase in the nominal load.…”
Section: Introductionmentioning
confidence: 99%
“…Schissler et al [15] and Owhadi et al [16] found that a low content of martensite in the microstructure (at a level of 0.1%), which had been formed as a result of the austenite transformation, had a positive impact on wear properties of cast irons. Myszka and Wieczorek [17] after having performed wear tests of three types of nodular cast iron with addition of Cu and Ni in corundum abrasive have found that the hardest cast iron has the best wear resistance, but strengthening of the surface apparently occurs in the material with the lowest hardness and best ductility that contained the highest amount of retained austenite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation